3-[6-(2-Chlorobenzoyl)-2-oxo-2,3-dihydro-1,3-benzothiazol-3-yl]propanenitrile - Aydin, Abdullah; Akkurt, Mehmet; Onkol, Tijen; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2006)
The title compound, C17H11ClN2O2S, crystallizes with two crystallographically independent molecules in the asymmetric unit. In the molecular structure, there are intramolecular weak C—H⋯O hydrogen bonds, which consolidate the molecular conformation.